Outcomes of percutaneous endoscopic lumbar discectomy via transforaminal approach in stable low-grade single level lumbar spondylolisthesis: a retrospective study - Chaichompoo, Thippatai; Wichan, Woraphot; Suvithayasiri, Siravich (International Journal of Research in Orthopaedics, 2026)
Background: Lumbar spondylolisthesis (LS) is a common degenerative spinal disease treated by fusion. Percutaneous endoscopic lumbar discectomy (PELD) reduces damage to tissues, blood loss, and hospital stay. Transforaminal PELD in stable low-grade LS has limited clinical and radiological outcomes, and inpatient department (IPD) cost comparisons with transforaminal lumbar interbody fusion (TLIF) are rare. This study evaluated clinical and radiographic outcomes and PELD versus TLIF IPD cost. Methods: This retrospective study included 24 patients with stable low-grade single-level LS who underwent transforaminal PELD between December 2021 and November 2022. Clinical outcomes were assessed using visual analogue scale (VAS), Oswestry disability index (ODI), modified MacNab criteria, walking distance improvement, and patient satisfaction. Radiographic outcomes were evaluated by percentage slip preoperatively and at final follow-up. IPD costs were compared between PELD and TLIF. Results: The mean age was 52 years, and L4-5 was the most common level. All patients had Grade 1 spondylolisthesis. Mean operative time was 53.17±26.14 minutes, blood loss was 8.29±10.45 mL, hospital stay was 2.96±1.16 days, and follow-up was 6.7 months. VAS, ODI, and walking distance improved significantly (p<0.001). Modified MacNab outcomes were excellent in 75% and good in 20.8%. Mean slip percentage showed no significant change (p=0.458). Mean IPD cost was 64,785.95 THB (1,754.69 EUR) for PELD and 98,392.36 THB (2,664.90 EUR) for TLIF. Conclusions: Transforaminal PELD is a safe and effective minimally invasive option for stable low-grade single-level LS, providing favorable short-term outcomes without radiographic progression and lower IPD cost than TLIF.